Soilless culture technology for protected environment agriculture (PEA): the need for mechanization and automation - Ismail, Mohd Razi; Megat Wahab, Puteri Edaroyati (Universiti Putra Malaysia, 1999)
Protected environment agriculture system for horticultural crop cultivation has widely been used in most developed countries. There is a growing demand for the introduction of this system in Malaysia to meet several objectives. The technology for crop production within the agriculture system has well been investigated to suite the local microclimatic and technological advancement requirements. Since the introduction of the system in early 80’s there is lack of research in mechanization and automation within this agricultural system. Hydroponics or soilless culture technology is commonly used in protected environment. One of the features in the system is that it offers programmable crop production. In Nutrient Film Technique system, for e.g., moveable gullies provide efficient labor usage. Information on the microclimatic factors and used of electronics for regulating cultural practices result to efficient crop management and reduce operational cost. The scope for mechanization and automation of hydroponics and soilless culture system will be highlighted.